MEDIA DISCOURSE AS RESEARCH MATERIAL FOR BILINGUAL LINGUISTIC IDENTITY STUDIES - Tulusina, Elena; Mordvinova, Albina; Sadykova, Aida; Med, Natalia (Revista Inclusiones, 2019)
The article presents the results of studying the possibility of using media discourse within the framework of studies of the features of the discourse of a bilingual linguistic identity. The authors of the article offer their own vision of the features of determining bilingualism in the discursive space and substantiate the maximum expediency of using the media discourse of the bilingual regions for an objective and comprehensive study of the linguistic and pragmatic features of the discourse of the bilingual linguistic identity. Such characteristics of media discourse are considered as publicity, interdiscourse, multi-genre, heterogeneity, interactivity and dialogue, coverage of institutional and personal discourse, etc.